2022
DOI: 10.1039/d1ta09021f
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous dual pyrolysis synthesis of heterostructured FeCo/C porous hollow microspheres for highly efficient microwave absorption

Abstract: Due to their multiple dissipation mechanisms, low density and easy tailored impedance matching, heterogeneous hollow structures are promising candidates for microwave absorbents towards wideband absorption and lightweight design. In this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…After the addition of BN nanoparticles, the FCBN composite shows the best performance with its maximum peak close to 1 at frequencies of 10.2 and 12.0 GHz; this frequency range is found in the effective bandwidth (RL < −10.0 dB) at thickness of 1.6 mm. In addition, the attenuation constant was calculated using the following equation to further describe the loss capacity of EMW absorbing materials: The α for all samples increases all over the frequency range as shown in Figure S5. The FCBN shows the highest α values, indicating the highest attenuation ability compared to the FeCo nanochains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the addition of BN nanoparticles, the FCBN composite shows the best performance with its maximum peak close to 1 at frequencies of 10.2 and 12.0 GHz; this frequency range is found in the effective bandwidth (RL < −10.0 dB) at thickness of 1.6 mm. In addition, the attenuation constant was calculated using the following equation to further describe the loss capacity of EMW absorbing materials: The α for all samples increases all over the frequency range as shown in Figure S5. The FCBN shows the highest α values, indicating the highest attenuation ability compared to the FeCo nanochains.…”
Section: Resultsmentioning
confidence: 99%
“…The FCBN shows the highest α values, indicating the highest attenuation ability compared to the FeCo nanochains. The synergetic effect of impedance matching and attenuation ability of FCBN leads to an effective absorption performance . In summary, the exceptional absorption performance is the result of the following comprehensive effects: (1) magnetic material loss from shape modulation and (2) interfacial/dipole polarization loss from the inclusion of a dielectric material. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, great efforts have been made in the manufacture of high-performance microwave absorbers for electronic information security and radar stealth technology. [1][2][3][4][5][6][7] Generally, the microwave absorption (MA) performance of an absorber depends on the matching degree of its electromagnetic characteristics with free space and its internal attenuation ability, both of which can be modulated by microstructure designs. [8][9][10] In the MA eld, the three-dimensional (3D) hierarchical structure doped with magnetic components can be constructed using zero-dimensional (0D), one-dimensional (1D) and twodimensional (2D) basic units, and has garnered considerable attention among various structures due to its synergistic advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al reported FeCo/C hybrids with an excellent RL of −58.69 dB. [39] And CuNi alloy/carbon foam prepared by Liu's group existed a great RL of −50.20 dB. [40] Despite these achievements, it still lacks a precise regulation approach of ferromagnetic alloy components and microstructures of carbon matrix, hence hindering the optimization of absorption performance and the comprehension of the electromagnetic wave absorbing mechanism for the magneticdielectric hybrids.…”
Section: Introductionmentioning
confidence: 99%